Scanning setup for the investigation of fluorescence beam spectra - Kłonowski, Łukasz; Bereś-Pawlik, Elżbieta; Rząca, Marek; Czarnecki, Roman (Photonics Letters of Poland, 2010)
In this paper we describe the scanning setup for investigating refracted beam spectra from changed cancer tissues. A special mechanical construction enables us to position measurement sensors using step motors and a micrometric XY stage. A fiber sensor which has been made of special fiber that does not provide any self fluorescence has been used for the illumination and detection. Full Text: PDF References: B. W. Chwirot, W. Jędrzejczyk, Luminescencja tkanek – nowe narzędzie wykrywania i lokalizacji nowotworów, Toruń (1995). J. A. Kiernan, M. Wessendorf, Autofluorescence:Causes and cures, Toronto Western Research Institute, [DirectLink] B. Valeur, Molecular fluorescence – Principles and applications, Wiley – VCH, (2001). H. Zeng, A. McWillimas, S. Lam, "Optical spectroscopy and imaging for early lung cancer detection", Photodiagnosis and Photodynamic Therapy 1, 111-122 (2004). [CrossRef] W. Denk, J. Strickler, W. W. Webb, "Two-Photon Laser Scanning fluorescence Microscopy", Science 248, 73-76 (1990). [CrossRef] B. A. Flusberg, E. D. Cocker, W. Piyawattanametha, J. C. Jung, E. L. M. Cheung, M. J, Schnitzer, "Fiber-optic fluorescence imaging", Nature Methods 2, 12 (2005). [CrossRef] J. W. Lichtman, J. A. Conchello, Fluorescence microscopy, Nature Methods 2 (2005). [CrossRef]